Enhanced metal-insulator transition in freestanding VO2 down to 5 nm thickness - Han, Kun (2021)
Ultrathin freestanding membranes with a pronounced metal–insulator transition (MIT) have huge potential for future flexible electronic applications as well as provide a unique aspect for the study of lattice–electron interplay. However, the reduction of the thickness to an ultrathin region (a few nm) is typically detrimental to the MIT in epitaxial films, and even catastrophic for their freestanding form. Here, we report an enhanced MIT in VO2-based freestanding membranes, with a lateral size up to millimeters and the VO2 thickness down to 5 nm. The VO2 membranes were detached by dissolving a Sr3Al2O6 sacrificial layer between the VO2 thin film and the c-Al2O3(0001) substrate, allowing the transfer onto arbitrary surfaces. Furthermore, the MIT in the VO2 membrane was greatly enhanced by inserting an intermediate Al2O3 buffer layer. In comparison with the best available ultrathin VO2 membranes, the enhancement of MIT is over 400% at a 5 nm VO2 thickness and more than 1 order of magnitude for VO2 above 10 nm. Our study widens the spectrum of functionality in ultrathin and large-scale membranes and enables the potential integration of MIT into flexible electronics and photonics.